Irrigated Onion Production Efficiency in Humbo District, Southern Ethiopia - Alula Tafesse; Samuel Dema; Abrham Belay (Cogent Economics & Finance, 2023)
The study sought to establish the level of technical, allocative, and economic efficiencies in irrigated onion production in southern Ethiopia, as well as to identify the sources of inefficiencies. The cross-sectional data were obtained from a total of 165 random onion farmers selected from the Humbo area. The parametric stochastic frontier model was used to estimate technical, allocative, and economic efficiency levels, whilst the two-limit Tobit model was utilized to identify determinants of inefficiencies. The data acquired suited the Cobb-Douglas (CD) production function, with land, labor, fertilizer, and chemicals as input factors that had a positive and significant influence on irrigated onion production. The sampled onion farmers' technical, allocative, and economic efficiencies were determined to be 77, 88, and 68%, respectively. The model results indicated that the age of the farmers, years of education, and total farm financial gain were identified as important sources of irrigated onion production inefficiencies in the research area. The mean technical efficiency levels indicate that irrigated onion producer farmers in the research area may raise their output by 23% with present inputs and technology. Alternatively, farmers will reduce their average production price by 12% while maintaining the current level of output. It is based on this that there is room to improve the efficiency of irrigated onion production. Therefore, the government's policies and actions should focus on timely and quality agricultural input supply for onion farmers and backing them through availing of formal and informal educational services.
Keywords: 330; Ethiopia; irrigated onion; production efficiency; stochastic frontier model